The Study of the Location, Amount, and Composition of the Rudal Composition of The Alichalyk Field, as Well as the Justification of the Experimental Method and Research Objects of the Obtained Samples - Prof. Samadov A.U.; Nosirov N. I.; Suyarov J. U. (International Journal of Scientific Trends, 2024)
This article examines the location and quantities of the research object and its composition. The object is the Olchali mine, located in the Namangan region. The cherry plot is located on the northeastern side of the Kurama mountain range, in the lower reaches of the Govasai River. A special methodology for the technological study of mining ore has been developed based on many years of research. The study involved a mineralogical-petrographic study of the material composition and textural characteristics of all types of rocks, the degree of metasomatic changes, the identification of ore-bearing mineral associations, and their interrelationships.